2016
DOI: 10.1038/srep17735
|View full text |Cite
|
Sign up to set email alerts
|

SPECC1L deficiency results in increased adherens junction stability and reduced cranial neural crest cell delamination

Abstract: Cranial neural crest cells (CNCCs) delaminate from embryonic neural folds and migrate to pharyngeal arches, which give rise to most mid-facial structures. CNCC dysfunction plays a prominent role in the etiology of orofacial clefts, a frequent birth malformation. Heterozygous mutations in SPECC1L have been identified in patients with atypical and syndromic clefts. Here, we report that in SPECC1L-knockdown cultured cells, staining of canonical adherens junction (AJ) components, β-catenin and E-cadherin, was incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 51 publications
4
48
0
Order By: Relevance
“…Control and SPECC1L-kd U2OS cells were generated previously from U2OS osteosarcoma cells (ATCC HTB-96) as reported (Saadi et al 2011). U2OS cells were cultured in DMEM (HyClone, SH30243.01) containing 10% FBS (Corning, 35-010-CV) as shown previously (Wilson et al 2016).…”
Section: U2os Cell Culturementioning
confidence: 99%
See 3 more Smart Citations
“…Control and SPECC1L-kd U2OS cells were generated previously from U2OS osteosarcoma cells (ATCC HTB-96) as reported (Saadi et al 2011). U2OS cells were cultured in DMEM (HyClone, SH30243.01) containing 10% FBS (Corning, 35-010-CV) as shown previously (Wilson et al 2016).…”
Section: U2os Cell Culturementioning
confidence: 99%
“…We previously reported that loss of SPECC1L results in decreased PI3K-AKT signaling along with defects in cell-adhesion and cell-shape (Wilson et al 2016).…”
Section: Upregulation Of Pi3k-akt Signaling Rescues Specc1l-deficientmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2011, mutations in SPECC1L were identified in two patients with oblique facial clefts (Saadi et al, 2011). They were later also found in patients with Opitz G/BBB syndrome, the letters referring to the initials of patients first diagnosed with it, which is associated with cleft lip and/or palate (Kruszka et al, 2015), and in a family with Teebi hypertelorism syndrome, which is characterized by the presence of frontonasal dysplasia (Bhoj et al, 2015;Wilson et al, 2016). SPECC1L is a cytoskeletal protein that interacts with both microtubules and the actin cytoskeleton.…”
Section: Oblique Facial Cleft Syndromementioning
confidence: 99%